249 Relationships Between Sow, Litter, and Piglet Parameters and the Rectal Temperature of Piglets at Birth and 30 Min After Birth. (12th April 2022) - Vande Pol, Katherine D; Shull, Caleb M; Ellis, Michael
Abstract: The objective was to evaluate relationships between sow, litter, and piglet parameters and piglet rectal temperature at birth and 30 min after birth. Data (460 sows/litters; 1, 240 piglets) were from 5 studies conducted on the same commercial farrowing facility with the same management. Sow variables included parity and rectal temperature at start of farrowing, and use of farrowing induction. Piglet variables included birth weight, rectal temperature at 0 and 30 min after birth, birth interval (time from the birth of the previous piglet), birth order, and sex. Other variables included room temperature at start of farrowing and number of piglets born alive. Piglets were only handled to collect measurements; no interventions were used. Data were analyzed using PROC REG of SAS. Models accounted for the linear, quadratic, and cubic effects of each independent variable. Mean piglet temperature at birth and 30 min was 38.8 ± 0.55°C and 35.7 ± 1.35°C, respectively. For piglet birth temperature, all variables were related except farrowing induction and piglet sex (Table 1). The relationship with sow temperature at start of farrowing was positive and had the greatest R 2 value (0.18). For piglet 30 min temperature, all variables were related ( P ≤ 0.05) except sow parity, farrowing induction, and piglet sex (Table 1). The relationship with piglet birth weight was positive and had the greatest R 2 value (0.31). Multivariate models including all significant ( P ≤ 0.05) terms explained 35 and 50% of the variation in piglet birth and 30 min temperature, respectively. In conclusion, the primary factor affecting piglet birth and 30 min temperature was sow temperature and piglet birth weight, respectively. However, even when combining all of the factors, a large proportion of the variation in piglet temperature at both times remained unexplained.